Taj Mahal - Arnold, Caroline; Comora, Madeleine; Bhushan, Rahul (Minneapolis, Minnesota : Carolrhoda Books, 2007)
Recounts the love story behind the building of the Taj Mahal in India, discussing how it was constructed and providing information on Indian culture.
Includes bibliographical references (page [32]).
Also available in electronic resource.
Keywords: Taj Mahal (Agra, India) -- Juvenile literature; Architecture, Mogul -- India Agra -- Juvenile literature; Agra (India) -- Buildings,structures,etc. -- Juvenile literature; Electronic books (Form)